THE IMPORTANCE OF GRAPHIC IMAGES IN TRADITIONAL JAPANESE TATTOOS - Кротевич, О. В. (Art and Design, 2019)
Purpose. Consider, reveal, what value graphic images occupy in traditional modern Japanese artistic tattoo. The methodology of this study is to apply general scientific methods of comparative historical and image-stylistic analysis. Considered, analyzed and identified the main graphic images that affect the formation and preservation of traditional Japanese artistic tattoos. These are images: groups of flora (sakura flower or chrysanthemums, maple leaf), groups of fauna (dragon, tiger, carp) and national, heroic, mythological and religious images (samurai, demons and gods). These are the features of the Japanese tattoo: asymmetry, characteristic figures, shading of the decorative contour and its deep saturation, contrast, dynamics of each individual construction, filling the void with texts and hieroglyphs, dominance of the main graphic images, a combination of small motifs and pronounced large scale images. Given the dynamics of development and the prospects for the spread of artistic tattoos, the features of the influence of graphic images on the preservation of national traditions in modern Japanese tattoos are highlighted. This approach allows us to determine the trends in the development of modern tattoo.